Screening the medicines for Malaria Venture "Malaria Box" against the Plasmodium falciparum aminopeptidases, M1, M17 and M18 - Paiardini, Alessandro; Bamert, Rebecca S.; Kannan-Sivaraman, Komagal; Drinkwater, Nyssa; Mistry, Shailesh N.; Scammells, Peter J.; McGowan, Sheena (Public Library of Science, 2015)
Malaria is a parasitic disease that remains a global health burden. The ability of the parasite to rapidly develop resistance to therapeutics drives an urgent need for the delivery of new drugs. The Medicines for Malaria Venture have compounds known for their antimalarial ac- tivity, but not necessarily the molecular targets. In this study, we assess the ability of the “MMV 400” compounds to inhibit the activity of three metalloaminopeptidases from Plasmo- dium falciparum, PfA-M1, PfA-M17 and PfM18 AAP. We have developed a multiplex assay system to allow rapid primary screening of compounds against all three metalloaminopepti- dases, followed by detailed analysis of promising compounds. Our results show that there were no PfM18AAP inhibitors, whereas two moderate inhibitors of the neutral aminopepti- dases PfA-M1 and PfA-M17 were identified. Further investigation through structure-activity relationship studies and molecular docking suggest that these compounds are competitive inhibitors with novel binding mechanisms, acting through either non-classical zinc coordina- tion or independently of zinc binding altogether. Although it is unlikely that inhibition of PfA- M1 and/or PfA-M17 is the primary mechanism responsible for the antiplasmodial activity re- ported for these compounds, their detailed characterization, as presented in this work, pave the way for their further optimization as a novel class of dual PfA-M1/PfA-M17 inhibitors uti- lising non-classical zinc binding groups.